Predicao de campo em comunicacao sem fio - Moura, Carlos Gomes de (2011)
Even living in the XXI century are still some difficulties in access to broadband Internet in several Brazilian cities, due to the purchasing power of people and lack of government investment. But even with these difficulties, we seek to encourage the use of wireless technology, which is based on the IEEE 802.11b protocol - also known as Wi-Fi (Wireless Fidelity) Wireless Fidelity Communications, having wide range of commercial applications in the world market, nationally and internationally. In Brazil, this technology is in full operation in major cities and has proved attractive in relation to the access point to multipoint and point-to-point. This paper is a comparative analysis of prediction field, using models based on the prediction of propagation loss. To validate the techniques used here, the Okumura-Hata models, modified Okumura-Hata, Walfisch-Ikegami model, were applied to a wireless computer network, located in the neighborhood of Cajupiranga in the city of Melbourn, in Rio Grande do Norte . They are used for networking wireless 802.11b, using the Mobile Radio to measure signal levels, beyond the heights of the antennas and distances from the transmitter. The performance data versus distance are added to the graphs generated and compared with results obtained through calculations of propagation models